1)
2)
3)
1. 1/2;
2. √3/3;
3. 1.
Пошаговое объяснение:
1. cos(19π/3) = cos (6π + π/3) = cos(π/3) = 1/2;
2. tg(31π/6) = tg(5π + π/6) = tg(π/6) = √3/3.
3. ctg (13π/4) = ctg(3π + π/4) = ctgπ/4 = 1.
1)![cos \frac{19\pi }{3} = cos 6\frac{\pi }{3} = cos \frac{\pi }{3} = \frac{1}{2}](/tpl/images/1359/9276/3df74.png)
2)![tg \frac{31\pi }{6} = tg 5\frac{\pi }{6} = tg \frac{\pi }{6} = \frac{\sqrt{3} }{3}](/tpl/images/1359/9276/4088a.png)
3)![ctg \frac{13\pi }{4} = ctg 3\frac{\pi }{4} = ctg \frac{\pi }{4} = 1](/tpl/images/1359/9276/13440.png)
1. 1/2;
2. √3/3;
3. 1.
Пошаговое объяснение:
1. cos(19π/3) = cos (6π + π/3) = cos(π/3) = 1/2;
2. tg(31π/6) = tg(5π + π/6) = tg(π/6) = √3/3.
3. ctg (13π/4) = ctg(3π + π/4) = ctgπ/4 = 1.